Study Measuring Characteristic of the High Intensity Reverberation Acoustic Chamber Performance - Hidayah Tauhid Ahmad, Noor; Salim, Nurliza; Thanarasi, Karthigesu; Ismail, Maszlan (International Journal of Engineering and Technology, 2018)
Reverberation Acoustic Test Facility (RATF) is a one of the mechanical satellite testing facility in the Assembly, Integration and Test Centre at National Space Agency (ANGKASA). This is the reverberation type of chamber with external volume at 999.5m3, has the capability to regenerate high intensity acoustic noise ambiance that will be experienced during the launching stage. This paper will describe on reverberation chamber characteristics, the noise generating system and capabilities, and the chamber configuration for high intensity acoustic testing in empty chamber condition. This paper recommends the measurement setting for three variant spectrum levels in generating high-intensity acoustic noise from 130dB to 155dB with center frequencies from range 31.5Hz to 1250Hz.Â Â